Da'wah bi al-Hal in Empowering Campus-Assisted Community through Waste Bank Management - Mukti Ali; Saipullah Hasan (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2019)
As an institution of education and agent of social change, the Faculty of Da'wah, IAIN Salatiga, has Islamic religious characteristics. These characteristics confirm its missionary effort as a part of social responsibility. The Da'wah Faculty pursues empowerment by rolling out a program of waste bank management. This program is a manifestation of the application of da’wah bi al-hal (preaching by actuating) to build assisted-communities who are empowered and independent in processing garbage. Furthermore, the program of waste bank management not only provides clean and healthy communities but also increases the community’s ability to gain environmental benefits and improving its economy. This study aims to analyze the implementation of da’wah movement through waste bank management, from assessment, recycling management, construction, to evaluation. The method of research in this study uses a qualitative method, Participatory Action Research (PAR) to make changes and benefits for the community, and empowerment theory as the mainframe of thought in carrying out da’wah bi al-hal. The results of participatory action research showed that preaching by actuating of Da’wah Faculty IAIN Salatiga in the assisted-communities has increased participation, trust, and cooperative relationships among them in managing the waste bank. Fakultas Dakwah IAIN Salatiga sebagai lembaga pemikiran dan agen perubahan sosial, memiliki karakteristik keagamaan Islam. Karakteristik ini meneguhkan upaya berdakwah sebagai tanggung jawab sosialnya. Dalam melakukan dakwah di masyarakat, Fakultas Dakwah menempuh cara pemberdayaan dengan menggulirkan program pengelolaan bank sampah. Hal ini sebagai wujud aplikasi dakwah bi al-hal untuk membangun masyarakat binaan yang berdaya dan mandiri dalam mengolah sampah. Program pengelolaan bank sampah tidak hanya memberikan manfaat lingkungan bersih dan sehat, tetapi juga meningkatkan kemampuan masyarakat untuk mengolah sampah dalam meningkatkan perekonomian. Penelitian ini bertujuan untuk menganalisis tentang implementasi dakwah bi al-hal dengan program pengelolaan bank sampah itu berjalan mulai assesment, manajemen daur ulang, pembangunan sarpras dan evaluasi. Metode dalam penelitian ini menggunakan metode kualitatif Participatory Action Research (PAR) untuk melakukan perubahan dan manfaat bagi masyarakat dengan teori pemberdayaan sebagai kerangka berfikir utama dalam melakukan dakwah bi al-hal. Hasil penelitian aksi partisipatif memperlihatkan bahwa sentuhan pendampingan yang telah dilakukan Fakultas Dakwah IAIN Salatiga terhadap masyarakat binaannya dapat meningkatkan partisipasi, kepercayaan dan hubungan kerja sama diantara mereka dalam pengelolaan bank sampah.